Are oil price forecasters finally right? Regressive expectations toward more fundamental values of the oil price - Stefan Reitz; Jan-Christoph Rülke; Georg Stadtmann (Deutsche Bundesbank, 2009)
We use oil price forecasts from the Consensus Economic Forecast poll to analyze how forecasters form their expectations. Our findings seem to indicate that the extrapolative as well as the regressive expectation formation hypothesis play a role. Standard measures of forecast accuracy reveal forecasters' underperformance relative to the random walk benchmark. However, this result appears to be biased due to peso problems.
Keywords: F31; D84; C33; 330; Oil price; survey data; forecast bias; peso problem; Erdölpreis; Sachverständige; Erwartungstheorie; Prognose; Bias; Extremwertanalyse; Welt